miR-199a expression and its targets during development in different Arctic charr morphs - Ástrós Skúladóttir 1991- (2014)
The four morphs of Arctic charr in Þingvallavatn differ significantly in morphology, especially in their feeding apparatus. Given the evolutionary history of Arctic charr in Iceland it is likely that genes engaged in the formation of the craniofacial structures are expressed differentially between the morphs. miRNAs are known to play an important role in the differentiation and the development of the cartilage. miR-199a is of particular interest because it is highly conserved among vertebrates, exhibits a differential expression pattern in transcriptome data from different Arctic charr morphs and is reported to be specifically expressed in the skeletal system in other vertebrates. To gain a better understanding of the developmental processes miR-199a is involved in, which genes it interacts with and regulates, it is important to identify its mRNA targets. With this in mind the expression of miR-199a was studied during the embryonic development in the head of two Arctic charr morphs, large benthivorous and planktivorous using WISH at three developmental stages (177 DD, 200 DD and 238 DD). miR-199a was expressed in the craniofacial elements at all stages in both morphs and its expression decreased from the earliest to the latest stage as well as showing differences between the morphs. Four candidate mRNA targets were identified with computational approaches. Two of them (lum and ets2) were studied with WISH and showed similar patterns of expression as miR-199a in both morphs at stage 200 DD. miQPCR was also used to determine the expression differences of miR-199a between morphs although without success.